Severe Infections after Tooth Removal: a Retrospective Cohort Study - Klara Grønhøj; Rasmus Søndenbroe; Merete Markvart; Simon Storgård Jensen (eJournal of Oral Maxillofacial Research, 2025)
Objectives: The purpose of this retrospective cohort study was to determine the characteristics of patients hospitalized with severe infections after tooth removal.